Financial Automation Audit Method Based on Blockchain Technology. (5th July 2022) - Gai, Weidong; Gu, Yue; Qin, Jiaming
Abstract : Blockchain (BC) maintains a continuously growing database in a "decentralized" way, and its impact on the financial auditing industry is becoming increasingly significant. This paper aims to study the research on financial automation auditing methods supported by blockchain technology and proposes the related concepts of blockchain technology, hash function, financial auditing analysis, and the impact of BP Neural Network (BPNN) and its algorithms on financial automation auditing methods. Simultaneously, this paper likewise disperses the poll overview to definite individuals, for example, endeavor, monetary work force, focus and ranking directors, university researchers, and specialists, who have pragmatic support in the execution and use of monetary review. The experimental results of this paper show that speculation based on the interconnected environment is the most basic natural factor for understanding this idea, and its score is also the largest at 4.36 points.